Analysis of Abundance and Composition of Culturable Bacteria and Their Relationship with Water Quality Parameters in Intensive Shrimp Ponds - Gede Iwan Setiabudi; Kadek Lila Antara; Hamdanul Fain; Meutia Samira Ismet (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2026)
Intensive cultivation of Pacific white shrimp (Penaeus vannamei) is a crucial pillar of the aquaculture economy, but it faces sustainability challenges due to water-quality degradation driven by microbial activity. This study aims to analyze the total bacterial count (TBC) and total Vibrio count (TVC), identify the dominant culturable bacterial genera, and determine their statistical relationship with physicochemical water quality parameters in intensive shrimp ponds. The research methodology included regular sampling of water and sediment over one cultivation cycle. Water quality was analyzed using standard methods, while bacterial enumeration was performed using the spread plate technique on Marine Agar and Thiosulfate Citrate Bile Salts Sucrose Agar media. Pearson's correlation analysis was used to test the relationship between variables. The results show that some water quality parameters, particularly ammonia and TOM, tended to increase and exceed the SNI 01-7246-2006 quality standard as the cultivation cycle progressed. The abundance of TBC and TVC in sediment (average 106−107CFU/g) was significantly higher than in the water column (average 104−105 CFU/mL). Correlation analysis revealed a strong and significant negative relationship between DO and TBC (r=−0.85, p<0.01) and TVC (r=−0.79, p<0.01). Conversely, a strong and significant positive correlation was found between TOM and TBC (r=0.91, p<0.01) and TVC (r=0.88, p<0.01), as well as between ammonia and both TBC and TVC. It is concluded that the abundance of culturable bacteria, especially TBC and TVC, serves as a sensitive biological indicator of organic load and ecological stress in intensive pond systems. The strong predictive relationship between these microbial metrics and key parameters, such as DO and TOM, underscores the importance of microbiological monitoring for proactive management and improved sustainability in aquaculture.